Effect of alcoholic and cold aqueous extracts of Melia azedarch(L.) and Actellic insectiside in the second larval instars of Oryzaephilus surinamensis - Baghdad Science Journal (مجلة بغداد للعلوم)
The effect of alcoholic extract (2%,4%, 12%) and the fruits aqueous extract (12%,15%,25%,35%) of Melia azedarach and actellic insecticide of 0.01 concentration were tested on the second instar larvae ofOryzaephilus surinamensis .The obtained resuls were reveated that the highest kill ratio 80% at the concentration 12% of the alchoholic extract and 85% of the aqueous extract this was reflected effect abstracts on low rate of age adult emerging of larve treated and low productivity